Toxicological impact of the antibiotic norfloxacin on hematological, serum biochemical parameters, and hematopoietic system of Heteropneustes fossilis - Chandni; Abdur Rouf Samim; Huma Naz; Huma Vaseem (Ecotoxicology, 2026)

Suppression of necroptosis-driven cell death and inflammation in hypoxic neuroblastoma (SH-SY5Y) cells by necrostatin-1 - Amal Majed H. Alenad; Mohd Shahnawaz Khan; Nojood Al-twaijry; Majed S. Alokail; Leon Bernet Shano; Subramani Karthikeyan; Huma Naz; Bigyan Ranjan Jali (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Unveiling the Microplastics Menace in Freshwater Fishes: Evidence from the Panjnad Barrage, South Punjab, Pakistan - Syed Muhammad Moeen Uddin Raheel; Adnan Ahmad Qazi; Muhammad Latif; Huma Naz; Yasir Waqas; Maximilian Lackner (Fishes, 2025)
This study explored the prevalence and types of microplastic (MP) pollution in three fish species—Labeo rohita, Wallago attu, and Cirrhinus mrigala—collected from the Panjnad Barrage in South Punjab, Pakistan. MPs were analyzed from the gastrointestinal tracts (GITs), gills, and muscles of 90 fish samples. Advanced analytical techniques, including Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy/Energy-Dispersive X-Ray Spectroscopy (SEM/EDX), and Gas Chromatography/Mass Spectrometry (GC/MS), were deployed, confirming the polymeric composition and presence of various additives. Quantitative and qualitative analyses revealed significant variations in MP accumulation across tissues, with the GIT consistently showing the highest MP count, the gills having the highest concentration per gram, and the muscles exhibiting the lowest amount of accumulation. Wallago attu was found to have accumulated the highest concentration of microparticles among all three species due to its feeding habits and habitat. Fibers and fragments were the predominant types of MPs, with yellow and red being the most frequent colors. Polypropylene (PP) and polyethylene (PE) were the primary polymers identified, alongside other types like polyethylene terephthalate (PET) and polyvinyl chloride (PVC). The MP size distribution indicated that mid-sized particles (150–50 µm) were most abundant in the GIT and gills, while smaller particles (

Smart IoT-based snake trapping device for automated snake capture and identification - Neelu Jyothi Ahuja; Nitin Pasi; Huma Naz; Rahul Chamola (Environmental Monitoring and Assessment, 2025)

Evaluation of Hepatotoxic Potential of an Azo Dye, Eriochrome Black T on Freshwater Catfish, Clarias batrachus - Huma Naz; Huma Vaseem (Bulletin of Environmental Contamination and Toxicology, 2025)

Analysis of serum lead, copper, iron, and zinc and hematological parameters in battery smelting workers: assessing lead toxicity - Maleeha Sikandar Memon; Ikram Udiin Ujjan; Marvi Shaikh; Sadia Qamar Arain; Arshi Naz; Huma Abbasi (BioMetals, 2024)

Alteration in oxidative stress markers, digestive physiology and gut microbiota of Heteropneustes fossilis and Clarias batrachus exposed to eriochrome black T - Huma Naz; Huma Vaseem (Chemosphere, 2024)

Microsatellite and mtDNA-based exploration of inter-generic hybridization and patterns of genetic diversity in major carps of Punjab, Pakistan - Shakeela Parveen; Khalid Abbas; Muhammad Tayyab; Muhammad Hussain; Huma Naz; Laiba Shafique (Aquaculture International, 2024)

An efficient densenet-based deep learning model for Big-4 snake species classification - Huma Naz; Rahul Chamola; Jaleh Sarafraz; Mahdi Razabizadeh; Siddharth Jain (Toxicon, 2024)

Correction: Protective effect of didymin against 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin-induced reproductive toxicity in male rats - Arfa Tahir; Muhammad Umar Ijaz; Huma Naz; Tayyaba Afsar; Ali Almajwal; Houda Amor; Suhail Razak (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Protective effect of didymin against 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin-induced reproductive toxicity in male rats - Arfa Tahir; Muhammad Umar Ijaz; Huma Naz; Tayyaba Afsar; Ali Almajwal; Houda Amor; Suhail Razak (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

The Role of Cancer-Specific Target Antigens in CAR T Cell Therapy in Hematological Malignancies - Tabish H. Khan; Naoshad Muhammad; Mohammad Tarique; Darksha Usmani; Huma Naz; Aditya Sarode (Current Tissue Microenvironment Reports, 2024)

Mesorhizobium improves chickpea growth under chromium stress and alleviates chromium contamination of soil - Huma Naz; R.Z. Sayyed; Riyaj Uddin Khan; Asma Naz; Owais Ali Wani; Ayesha Maqsood; Samiya Maqsood; Ali Fahad; Shabbir Ashraf; Pau Loke Show (Journal of Environmental Management, 2023)

An automated unsupervised deep learning–based approach for diabetic retinopathy detection - Huma Naz; Rahul Nijhawan; Neelu Jyothi Ahuja (Medical & Biological Engineering & Computing, 2022)

Amelioration of lead toxicity by ascorbic acid in sugarcane (Saccharum officinarum L.) under in vitro condition - Yasmeen Saleem; Aamir Ali; Shagufta Naz; Muhammad Jamil; Naima Huma Naveed (Environmental Science and Pollution Research, 2022)

Anticancer potential of yohimbine in drug-resistant oral cancer KB-ChR-8–5 cells - Nasimudeen R. Jabir; Mohd Shahnawaz Khan; Nouf Omar Alafaleq; Huma Naz; Bakrudeen Ali Ahmed (Molecular Biology Reports, 2022)

Thermococcus kodakarensis-derived L-asparaginase: a candidate for the treatment of glioblastoma - Huma Naz; Sheereen Gull; Qamar Bashir; Naeem Rashid; Naveed Shahzad (Biologia, 2021)

Evidence of vanillin binding to CAMKIV explains the anti-cancer mechanism in human hepatic carcinoma and neuroblastoma cells - Huma Naz; Mohd Tarique; Parvez Khan; Suaib Luqman; Shahzaib Ahamad; Asimul Islam; Faizan Ahmad; Md. Imtaiyaz Hassan (Molecular and Cellular Biochemistry, 2018)